Journal Of Indonesia Economy & Bisnis = Jurnal Ekonomi & Bisnis Indonesia - Samsubar Saleh (Faculty of Economic & Business Universitas Gadjah Mada, 2010)
NO. Penulis ---- Judul Artikel ---- Halaman 1. Samsubar Saleh dan Tri Widodo ---- Trade Specialization Indices : Two Competing Models ---- 129-142 2. D.S. Priyarsono, Titi Kanti Lestari dan Diah Ananta Dewi ---- Industrialization and De-Industrialization in Indonesia 1983-2008 : A Kaldorian Approach ---- 143-154 3. Joy Elly Tulung ---- Global Determinants of Entri Mode Choice ---- 155-169 4. Haeryip Sihombing, ADi Saptari dan Mohd Yuhazri bin Yakoob ---- Business Strategies Through Fit Management of Human Capital as Competitive Advantage ---- 170-189 5. Untoro Widagdo, Yeni Asriwulan dan Ananda Sabil Hussein ---- The Application of E-Tourism in Small and Medium-Scale Tourism in Indonesia : A Strategic Management View ---- 190-200 6. Luciana Spica Almilia ---- Financial and Non Financial Factors Influencing Internet Financial and Sustainability Reporting (IFSR) in Indonesia Stock Exchange ---- 201-221 7. Haula Rosdiana ---- Reformulating Policy on Frequency Usage Fees as Non-Tax State Revenue : Urgency and Its Implications ---- 222-238 8. Y. Sri Susilo ---- Factors Affecting Food Security in Rural Areas in Yogyakarta Province ---- 239-250